Lactiplantibacillus plantarum–Nomad and Ideal Probiotic - Fidanza, Mario; Panigrahi, Pinaki; Kollmann, Tobias R. (Frontiers in Microbiology, 2021)
Probiotics are increasingly recognized as capable of positively modulating several aspects of human health. There are numerous attributes that make an ideal probiotic. Lactiplantibacillus plantarum (Lp) exhibits an ecological and metabolic flexibility that allows it to thrive in a variety of environments. The present review will highlight the genetic and functional characteristics of Lp that make it an ideal probiotic and summarizes the current knowledge about its potential application as a prophylactic or therapeutic intervention.